Proof: Get Begin Expr Value 13
Let's prove the following theorem:
if the following are true:
- expression state at time 13 = "begin_expr"
- the expression at time 13 =
__eq__(7, 9)
- Value Stack at time 13 = [ ]
then Value Stack at time 14 = [ [ ], [ ] ]
Proof:
Given
1 | expression state at time 13 = "begin_expr" |
---|---|
2 | the expression at time 13 = __eq__(7, 9) |
3 | Value Stack at time 13 = [ ] |
# | Claim | Reason |
---|---|---|
1 | Value Stack at time (13 + 1) = [ [ ], Value Stack at time 13 ] | if expression state at time 13 = "begin_expr" and the expression at time 13 = __eq__(7, 9) , then Value Stack at time (13 + 1) = [ [ ], Value Stack at time 13 ] |
2 | [ [ ], Value Stack at time 13 ] = [ [ ], [ ] ] | if Value Stack at time 13 = [ ], then [ [ ], Value Stack at time 13 ] = [ [ ], [ ] ] |
3 | Value Stack at time (13 + 1) = [ [ ], [ ] ] | if Value Stack at time (13 + 1) = [ [ ], Value Stack at time 13 ] and [ [ ], Value Stack at time 13 ] = [ [ ], [ ] ], then Value Stack at time (13 + 1) = [ [ ], [ ] ] |
4 | 13 + 1 = 14 | 13 + 1 = 14 |
5 | Value Stack at time (13 + 1) = Value Stack at time 14 | if 13 + 1 = 14, then Value Stack at time (13 + 1) = Value Stack at time 14 |
6 | Value Stack at time 14 = [ [ ], [ ] ] | if Value Stack at time (13 + 1) = Value Stack at time 14 and Value Stack at time (13 + 1) = [ [ ], [ ] ], then Value Stack at time 14 = [ [ ], [ ] ] |
Comments
Please log in to add comments